2006
DOI: 10.1523/jneurosci.2198-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Operant Conditioning of H-Reflex Can Correct a Locomotor Abnormality after Spinal Cord Injury in Rats

Abstract: This study asked whether operant conditioning of the H-reflex can modify locomotion in spinal cord-injured rats. Midthoracic transection of the right lateral column of the spinal cord produced a persistent asymmetry in the muscle activity underlying treadmill locomotion. The rats were then either exposed or not exposed to an H-reflex up-conditioning protocol that greatly increased right soleus motoneuron response to primary afferent input, and locomotion was reevaluated. H-reflex up-conditioning increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 52 publications
8
130
1
1
Order By: Relevance
“…Furthermore, muscular and kinematic analyses provide insight into the responsible mechanisms. The results illuminate the important role of the spinal cord in motor learning, and they support recent studies indicating that motor learning protocols that change the spinal cord can improve locomotion after spinal cord injury in both animals and humans (Chen et al 2006a; Thompson et al 2013). …”
supporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, muscular and kinematic analyses provide insight into the responsible mechanisms. The results illuminate the important role of the spinal cord in motor learning, and they support recent studies indicating that motor learning protocols that change the spinal cord can improve locomotion after spinal cord injury in both animals and humans (Chen et al 2006a; Thompson et al 2013). …”
supporting
confidence: 85%
“…[H-reflex conditioning is comparable in male and female rats (Chen and Wolpaw 1995, 1996, 1997, 2006a, 2006b, 2006c.] All procedures satisfied the "Guide for the Care and Use of Laboratory Animals" (National Academies Press, Washington, DC, 2011) and had been reviewed and approved by the Institutional Animal Care and Use Committee of the Wadsworth Center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that with operant conditioning, rats with partial SCI can learn to use descending drive to regulate soleus H-reflex gains in a manner that can influence and possibly improve locomotor performance (Chen et al 2005(Chen et al , 2006. Similar operant conditioning protocols have been used in human SCI subjects to downregulate hyperactive spinal stretch reflexes in the upper limb (Segal and Wolf 1994) and suggest that such training may be valuable for improving motor performance.…”
Section: Volitional Influence On Feedback Modulation Of Gaitmentioning
confidence: 99%
“…Using H-reflex training in incomplete SCI in a rat model, Wolpaw 3 and Chen and colleagues 60 have now demonstrated that device-based training can promote gait compensation. The use of devices in combination with residual plasticity and function to steer plastic changes in appropriate directions is a very exciting prospect.…”
Section: Stimulation To Activate Residual Functionsmentioning
confidence: 99%